Changes in mouse thymus after exposure to tube-restraint stress - Drljača, Jovana N.; Vejnović, Ana-Marija T.; Miljković, Dejan M.; Popović, Milan J.; Rakić, Dušica B.; Sekulić, Slobodan R.; Čapo, Ivan Đ.; Petković, Branka B. (Archives of Biological Sciences, 2020)
Paper description: The thymus is the primary lymphoid organ sensitive to various types of stress that induce its atrophy. The effect of repeated tube-restraint stress 2 h daily for 10 or 20 consecutive days was studied on the weight, proliferation and apoptosis of the thymus in mice. A significant reduction in thymus weight accompanied by decreased cellularity and pronounced atrophy of its cortical part was observed. These changes were the same regardless of whether the stress lasted 10 or 20 days. These findings provide a more comprehensive view of repeated tube-restraint, with special emphasis on its duration, on stress-induced thymus atrophy. Abstract: The thymus is the primary lymphoid organ involved in the regulation of the immune and endocrine systems. It is particularly sensitive to various types of stress, which induce its atrophy. This study deals with the effect of repeated restraint stress on the weight, proliferation and apoptosis of the thymus in mice. During restraint, the animals were placed in 50-mL conical plastic tubes for 2 h every day for either 10 or 20 consecutive days. A significant reduction in thymus weight along with decreased cellularity and pronounced atrophy of the cortical part of the thymus was observed in animals exposed to repeated tube-restraint stress for 10 and 20 consecutive days. The observed changes in the thymus were the same, regardless of the number of days of exposure to stress. These findings provide a more comprehensive view of repeated tube-restraint, with special emphasis on its duration on stress-induced thymus atrophy. The presented findings could serve as a basis for further studies aimed at identifying the mechanisms responsible for the adaptive response of the thymus after repeated exposure to stress. https://doi.org/10.2298/ABS190716060D Received: July 16, 2019; Revised: August 27, 2019; Accepted: September 10, 2019; Published online: September 13, 2019 How to cite this article: Drljača J, Vejnović AT, Miljković DM, Popović MJ, Rakić DB, Sekulić SR, Čapo IĐ, Petković BB. Changes in mouse thymus after exposure to tube-restraint stress. Arch Biol Sci. 2020;72(1):5-11.